IPOs and Stock Returns: The Role of Capital Structure, Firm Size, Profitability, and Firm Value - Andiyanto, Stevanus; Amir; Edi Joko Setyadi; Selamet Eko Budi Santoso (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2025)
The aim of this research is to empirically test the relationship between stock returns and capital structure, company size, profitability and company value. The population in this study are companies that conducted an Initial Public Offering (IPO) on the Indonesia Stock Exchange (BEI) in 2020-2023. The sample was determined using the purposive sampling method. Data were analyzed using panel data analysis techniques. The results of this study found that company size has a positive effect on stock returns, while capital structure and profitability have no effect on stock returns and company value has a negative effect on stock returns.